Scrutinizing Vocabulary And Grammar Presentation In English Textbooks: A Comparative Evaluation - Nursyahrifa Nursyahrifa (Indonesian Journal of Educational Studies, 2026)
Abstract. This study aims to evaluate the presentation of vocabulary and grammar in two English textbooks designed for tenth-grade senior high school students, as these components play a fundamental role in language learning. Employing a descriptive qualitative research design, the study analyzed textbooks published by Erlangga and the Indonesian Ministry of Education and Culture. The materials and instructions in each unit were examined using an evaluation checklist synthesized from established textbook evaluation frameworks proposed by several experts. The analysis focused on how vocabulary and grammar were presented, sequenced, and recycled throughout the textbooks. The findings revealed that Bahasa Inggris obtained a higher overall score than Pathway to English. However, Pathway to English performed better in several grammar-related criteria, particularly in providing clearer grammar explanations and placing greater emphasis on language form. The results indicate that both textbooks possess distinct strengths and weaknesses in vocabulary and grammar presentation. The study provides pedagogical insights for teachers in adapting instructional materials and for textbook authors in improving future textbook development.  Keywords: textbook evaluation, vocabulary presentation, grammar presentation, English textbooks, comparative evaluation